Identification of the novel HLA‐A*02:01:204 allele by next‐generation sequencing. (3rd January 2023) - Ananeva, Anastasiia; Aboishava, Lizaveta; Dmitriev, Oleg; Yakovleva, Alika; Shagimardanova, Elena
Abstract : The novel HLA‐A*02:01:204 allele was characterized using next generation sequencing technology.